Effect of Lemongrass Essential Oil Vapors on Microbial Dynamics and Listeria monocytogenes Survival on Rocket and Melon Stored under Different Packaging Conditions and Temperatures - Agni Hadjilouka; Melissanthi Polychronopoulou; Spiros Paramithiotis; Periklis Tzamalis; Eleftherios H. Drosinos (Microorganisms, 2015)
The aim of the present study was to examine the effect of lemongrass essential oil vapors on the dynamics of surface microbiota and L. monocytogenes growth on rocket and melon under different packaging conditions and storage temperature. For that purpose, rocket and melon were placed on Expanded Polystyrene (EPS) trays, sprayed with L. monocytogenes to a population of 4.5–5.0 log CFU·g−1, packaged using microperforated Oriented Polypropylene (OPP) film in either air or Microperforated Active Modified Atmosphere (MAMA) (initial atmosphere 5% O2, 10% CO2) including a Whatman paper containing the essential oil, without contact with the product, and stored at 0, 5, 10, and 15 °C. Application of lemongrass exhibited a bactericidal effect on enterococci and a fungistatic effect on yeast-mould populations but only during air storage of rocket. The former took place at all temperatures and the latter only at 10 and 15 °C. No effect on shelf life of both products was recorded. However, an important effect on the sensorial properties was observed; during the first 4–5 days of storage both products were organoleptically unacceptable. Regarding MAMA packaging, it affected only Pseudomonas spp. population resulting in a reduction of 1–2 log CFU·g−1 in both products.